2018
DOI: 10.1186/s13104-018-3313-x
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for expanding community exercise programs incorporating a healthcare-recreation partnership for people with balance and mobility limitations: a mixed methods evaluation

Abstract: ObjectiveTo increase access to safe and appropriate exercise for people with balance and mobility limitations, community organizations have partnered with healthcare providers to deliver an evidence-based, task-oriented group exercise program in community centers in Canada. We aimed to understand challenges and solutions to implementing this program model to inform plans for expansion.ResultsAt a 1-day meeting, 53 stakeholders (healthcare/recreation personnel, program participants/caregivers, researchers) iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…The remaining sixteen studies in this review reported on the barriers and/or facilitators to participation in, or implementation of, an exercise intervention after stroke from the perspectives of staff. Examples of these interventions were 'exercise programme' [51], 'community-based exercise' [52,53], 'high intensity interval training' [54] and 'fitness programmes' [55] . These were included under this review's broad definition of aerobic exercise to avoid the possibility of excluding valuable data.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining sixteen studies in this review reported on the barriers and/or facilitators to participation in, or implementation of, an exercise intervention after stroke from the perspectives of staff. Examples of these interventions were 'exercise programme' [51], 'community-based exercise' [52,53], 'high intensity interval training' [54] and 'fitness programmes' [55] . These were included under this review's broad definition of aerobic exercise to avoid the possibility of excluding valuable data.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Staff included healthcare professionals [52,53,[58][59][60][61][62], physiotherapists [54,63,64] and fitness instructors [53,65], cardiac and stroke rehabilitation teams [66], exercise professionals [51,62] and others [53,[55][56][57]62]. The views of physiotherapists (n=909) were predominant with a lesser number of exercise professionals (n=114), medical staff (n=8) and nurses (=11) represented.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementing community-based exercise programs remains challenging [9], with a lack of published information on how to provide local contextualisation while keeping fidelity to essential elements [10]. Developing methods to assist community-based organizations to uptake established exercise evidence to routine practice while maintaining fidelity may be the most helpful way to advance decision making in this area.…”
Section: Introductionmentioning
confidence: 99%